Alisol B 23-acetate attenuates CKD progression by regulating the renin–angiotensin system and gut–kidney axis - Hua Chen; Min-Chang Wang; Yuan-Yuan Chen; Lin Chen; Yan-Ni Wang; Nosratola D. Vaziri; Hua Miao; Ying-Yong Zhao (Therapeutic Advances in Chronic Disease, 2020)
Background: Increasing evidence suggests a link between the gut microbiome and various diseases including hypertension and chronic kidney disease (CKD). However, studies examining the efficacy of controlling blood pressure and inhibiting the renin–angiotensin system (RAS) in preventing CKD progression are limited. Methods: In the present study, we used 5/6 nephrectomised (NX) and unilateral ureteral obstructed (UUO) rat models and cultured renal tubular epithelial cells and fibroblasts to test whether alisol B 23-acetate (ABA) can attenuate renal fibrogenesis by regulating blood pressure and inhibiting RAS. Results: ABA treatment re-established dysbiosis of the gut microbiome, lowered blood pressure, reduced serum creatinine and proteinuria, suppressed expression of RAS constituents and inhibited the epithelial-to-mesenchymal transition in NX rats. Similarly, ABA treatment inhibited expression of collagen I, fibronectin, vimentin, α-smooth muscle actin and fibroblast-specific protein 1 at both mRNA and protein levels in UUO rats. ABA was also effective in suppressing activation of the transforming growth factor-β (TGF-β)/Smad3 and preserving Smad7 expression in both NX and UUO rats. In vitro experiments demonstrated that ABA treatment inhibited the Wnt/β-catenin and mitochondrial-associated caspase pathways. Conclusion: These data suggest that ABA attenuated renal fibrosis through a mechanism associated with re-establishing dysbiosis of the gut microbiome and regulating blood pressure, and Smad7-mediated inhibition of Smad3 phosphorylation. Thus, we demonstrate ABA as a promising candidate for treatment of CKD by improving the gut microbiome and regulating blood pressure.